Bericht über Forschungen in den zentralen Anden, insbesondere im Titicacabecken - Monheim, Felix (ERDKUNDE, 1955)
One aim of this research expedition was to carry out an agricultural-geographical comparison between the Alps and the tropical Andes, using as examples the Rimac valley and the Lake Titicaca basin. It showed that in the altitudinal zoning of arable farming, despite many common features, there are nevertheless important principal differences. These are caused by the different climatic character of which the most notable feature in the Andes is the absence of seasons of different temperatures. The great altitude of the upper limit of cultivation is surprising; barley is for instance still grown at Poto (4,700 m.). This expedition served first of all to collect subject matter in preparation for a regional treatment of the Lake Titicaca basin. To this end geomorphological observations were made, such as distribution of certain types of relief, and those which would serve to elucidate the origin of Lake Titicaca, as well as studies of the hydrography, climate and vegetation cover. Of particular importance were investigations of the cultural geography, especially studies of the aboriginal Indian, the colonial Spanish and the modern type of agriculture. Each of these three epochs has contributed characteristic features to the landscape. In some places the communal possession of arable land has still survived from ancient Indian times, and frequently also the division into open fields (Zelgen) together with communally regulated cropping (Flurzwang). In agricultural implements too, many of Indian origin are still to be found. The occupation by the Spaniards resulted first and fore most in changes in the type of animal husbandry practised, as well as changes in conditions of land ownership. During the most recent past a modern development has gained momentum, causing considerable social tension, viz. agricultural reform in Bolivia. In spite of the great altitude of almost 4,000 m., agriculture is of a relatively high intensity and is responsible for a surprisingly high population density near the lake; e.g. the population density of the Island of Amantani is about 170 per sq.Km. Special attention is given to the dwellings. Besides the adobe houses with gabled grass-covered roofs, at some places near the lake ancient-looking, pyramid-shaped houses are found which are built entirely of turf. The author shows that they are relics of an older house type which was formerly more widely distributed within the Lake Titicaca basin. Because they withstand flooding more readily than the adobe houses, they have been able to survive until today in some of the areas liable to flood.